Forecasting of entropy production due to buoyant convection using support vector machines (SVM) in a partially cooled square cross-sectional room - Varol, Yasin; Öztop, Hakan Fehmi; Koca, Ahmet; Avci, Engin (Pergamon-Elsevier Science Ltd, 2009)
Forecasting of entropy generation of laminar natural convection in a partially cooled square cross-sectional room has been performed using support vector machines (SVM). The two-dimensional room was modeled as floor heating story with a window. Values of temperature and velocities were obtained by solving governing equations of natural convection with finite difference technique and using these values entropy generation was calculated with its definition. Forecasting of entropy generation clue to fluid friction irreversibility (FFI) and heat transfer irreversibility (HTI) were made with known values for unknown parameters using SVM. Thus, calculation time was extremely reduced and values were obtained even for non-convergence cases. It was observed that the SVM was a strong method to predict the entropy generation without computational fluid dynamic analysis for all cases. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Support vector machines; Entropy generation; Enclosure; Natural convection